RECONSTRUCTIVE PLASTIC SURGERY FOR BREAST CANCER (Innovate Conferences, 2025)
Breast cancer is the most common oncological disease among women both in Uzbekistan and worldwide. The development and implementation of modern diagnostic and treatment methods for breast cancer have led to an increase in the number of patients and higher quality of life requirements for those with breast cancer. This, in turn, has stimulated the development of a multidisciplinary approach to individualized and minimally invasive comprehensive treatment, with the most aesthetically pleasing procedures. Single-stage reconstruction after mastectomy is the immediate restoration of the breast during mastectomy. This allows a woman to avoid psychological discomfort and a second anesthesia, improving her quality of life and restoring a natural breast appearance in a single surgical procedure. Reconstruction can be performed using implants or the patient's own tissue (flap plastic surgery). We prefer organ-preserving oncoplastic surgeries, and if a mastectomy is necessary , single-stage reconstructions using implants or autologous tissue. The choice of surgical option depends on the size and location of the tumor, the size and condition of the glandular parenchyma, the severity of ptosis, the initial asymmetry, and the patient's wishes. The article presents principles of resection margin control, non-palpable tumor locations, regional staging principles , patient rehabilitation, and the selection and main options for skin-sparing procedures. mastectomies and one-stage reconstructions.